2018
DOI: 10.1021/jacs.7b13387
|View full text |Cite
|
Sign up to set email alerts
|

Anodically Coupled Electrolysis for the Heterodifunctionalization of Alkenes

Abstract: The emergence of new catalytic strategies that cleverly adopt concepts and techniques frequently used in areas such as photochemistry and electrochemistry has yielded a myriad of new organic reactions that would be challenging to achieve using orthodox methods. Herein, we discuss the strategic use of anodically coupled electrolysis, an electrochemical process that combines two parallel oxidative events, as a complementary approach to existing methods for redox organic transformations. Specifically, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(96 citation statements)
references
References 41 publications
2
92
0
1
Order By: Relevance
“…Using an electrochemical approach, we recently developed a method for the chlorotrifluoromethylation of alkenes using commercially available Langlois reagent (CF 3 SO 2 Na) and MgCl 2 as functional group donors and Mn(OAc) 2 as a catalyst (Scheme A) . The proposed mechanism entails the parallel oxidative generation of two open‐shell intermediates, CF 3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an electrochemical approach, we recently developed a method for the chlorotrifluoromethylation of alkenes using commercially available Langlois reagent (CF 3 SO 2 Na) and MgCl 2 as functional group donors and Mn(OAc) 2 as a catalyst (Scheme A) . The proposed mechanism entails the parallel oxidative generation of two open‐shell intermediates, CF 3 .…”
Section: Methodsmentioning
confidence: 99%
“…This radical is highly unstable (bond dissociation energy of an alkenyl C−H bond is approximately 110 kcal mol −1 ) and can in principle participate in a variety of side reactions. In our previous studies, we demonstrated that an sp 3 carbon‐centered radical can be efficiently captured by [Mn III ]−Cl to form a C−Cl bond . We reasoned that this Mn‐bound latent Cl radical would also react with an alkenyl radical and that the efficiency and selectivity of this atom transfer process could be controlled by tuning the ligand on the metal center.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrosynthesis, which can avoid the external oxidants by employing the electrons to achieve the redox reaction, is considered as a versatile and eco‐friendly synthetic strategy and has experienced remarkable renaissance in recent years . The electrochemical alkene difunctionalization is emerging as a approach to construct C−C, C−N, C−O, C−Cl and so on . We envisioned acyclic 1,3‐dicarbonyl compounds, which has interested the chemists over the years due to the high oxidation potential of acyclic 1,3‐dicarbonyl compounds, might serve as C‐radical sources and nucleophilic oxygen sources to react with alkenes, achieving the electro‐oxidative [3+2] annulation with hydrogen evolution.…”
Section: Methodsmentioning
confidence: 99%
“…Die Autoren nutzten hierzu einen elektrochemischen Ansatz mit Mn III -Chlorid als Cl-Atom-Transfer-Reagenz. [144]…”
Section: Manganunclassified